Electrocatalysis: Hollow Carbon Nanopolyhedra for Enhanced Electrocatalysis via Confined Hierarchical Porosity (Small 23/2017). Issue 23 (June 2017) - Song, Xiaokai; Guo, Linli; Liao, Xuemei; Liu, Jian; Sun, Jianhua; Li, Xiaopeng
Abstract : In article number1700238, Jianhua Sun, Xiaopeng Li, and co‐workers, report a hollow cobalt and nitrogen co‐doped carbon nanopolyhedra catalyst derived from a MOF that effectively traps O2 molecules available in the electrolyte. The hollow structure enables significant improvement in oxygen reduction reaction kinetics and stability. New insights into the spatial confinement effect and new guidelines to design electrocatalysts are presented.